Mapping the landscape of cognitive development in children with epilepsy. (May 2015) - Kellermann, Tanja S.; Bonilha, Leonardo; Lin, Jack J.; Hermann, Bruce P.
Abstract: Objective: Normal childhood development is defined by age-dependent improvement across cognitive abilities, including language, memory, psychomotor speed and executive function. Epilepsy is often associated with a global disruption in cognitive development, however, it is still largely unknown how epilepsy affects the overall organization of overlapping cognitive domains. The aim of the study was to evaluate how childhood epilepsy affects the developmental interrelationships between cognitive domains. Methods: We performed a comprehensive assessment of neuropsychological function in 127 children with new onset epilepsy and 80 typically developing children matched for age, gender, and socio-demographic status. A cross-correlation matrix between the performances across multiple cognitive tests was used to assess the interrelationship between cognitive modalities for each group (patients and controls). A weighted network composed by the cognitive domains as nodes, and pair-wise domain correlation as links, was assessed using graph theory analyses, with focus on global network structure, network hubs and community structure. Results: Normally developing children exhibited a cognitive network with well-defined modules, with verbal intelligence, reading and spelling skills occupying a central position in the developing network. Conversely, children with epilepsy demonstrated a less well-organized network with less clear separation between modules, and relative isolation of measures of attention and executive function. Conclusion: Our findings demonstrate that childhood-onset epilepsy, even within its early course, is associated with an extensive disruption of cognitive neurodevelopmental organization. The approach used in this study may be useful to assess the effectiveness of future interventions aimed at mitigating the cognitive consequences of epilepsy.